2017
DOI: 10.1182/bloodadvances.2017004317
|View full text |Cite
|
Sign up to set email alerts
|

Not just a marker: CD34 on human hematopoietic stem/progenitor cells dominates vascular selectin binding along with CD44

Abstract: Key Points• Human HSPCs expressing CD34 exhibit E-selectin binding activity, whereas those lacking CD34 do not.• CD34 is a unique E-and P-selectin ligand on human HSPCs that binds with kinetics comparable to other known selectin ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 90 publications
4
96
0
Order By: Relevance
“…Proliferation and differentiation of hematopoietic stem/progenitor cells are known to depend on specific local microenvironment formed by bone marrow vascular niches [ 5 , 6 ]. Endothelium of bone marrow is found to express cell adhesion molecules involved in cell signaling by interaction with glycoprotein and glycolipid ligands of HSPCs [ 6 , 7 , 8 ]. Recently, it was shown that selectins and integrins play a crucial role in regulation of hematopoiesis in experimental animals with myelosuppression after chemotherapy [ 9 , 10 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation and differentiation of hematopoietic stem/progenitor cells are known to depend on specific local microenvironment formed by bone marrow vascular niches [ 5 , 6 ]. Endothelium of bone marrow is found to express cell adhesion molecules involved in cell signaling by interaction with glycoprotein and glycolipid ligands of HSPCs [ 6 , 7 , 8 ]. Recently, it was shown that selectins and integrins play a crucial role in regulation of hematopoiesis in experimental animals with myelosuppression after chemotherapy [ 9 , 10 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cell-by-cell analysis and mixture modeling suggests that this ensemble average does not capture the subpopulations having high-PDGFR plasma membrane localization: 66 and 16% of mouse tumor EC-like cell membrane had ~23,400 PDGFRα and ~19,800 PDGFRβ, respectively (Figure 2F ). This significant heterogeneity may be attributed to the use of the CD34 marker to designate EC-like cells, because it is also found on stem cells/precursors, mast cells, and neurons (Nielsen and McNagny, 2008 ; Imoukhuede and Popel, 2014 ; AbuSamra et al, 2017 ). PDGFRα is also considered an important mesenchymal stem cell marker (Farahani and Xaymardan, 2015 ).…”
Section: A New Approach For Examining Gbm Heterogeneitymentioning
confidence: 99%
“…However, robust data highlight a CD34 expression not only by MSCs but by several other non-hematopoietic cell types [37]. The CD34 positive cells may define a specific subset of progenitor cells with enhanced adhesive and homing properties, which are likely to mimic lymphocyte homing to the inflammatory sites [38,39].…”
Section: Discussionmentioning
confidence: 99%